A review on application of IOT in paddy and oil palm plantation in Malaysia / Imnie Fadzlan Mat Jani - Mat Jani, Imnie Fadzlan (Faculty of Plantation and Agrotechnology, 2019)
The Industrial Revolution was the improvement from the old manufacturing to the better manufacture processes. Involvement of internet in every sector are leading to the development of a country and achieving the vision of industrial revolution which is reducing manpower used. In Malaysia, agriculture is the next major contributor to the country after engineering sector. There are four major crop plantations in Malaysia and two of them are paddy and oil palm which are the commodity in international market. The global demand of rice and palm oil cannot be fulfil if our country are still fully depends on labour force and it will give a huge impact to the economy. There are several components of IOT and technology facilitate farmers to get high production but are not practically applied in Malaysia. This study was conducted to study the components and technology of IOT in agriculture sector and its application in paddy and oil palm plantation which help farmers to gain high yield without involving high manpower. The implementation of in paddy helps farmers to get uniform spraying of pesticide while the application Soil EC Mapping help farmers to collect information of soil before planting and both of these technologies help them to reduce the usage of manpower. This is the reason why Malaysia should emphasize this application of technology to raise the productivity of agricultural sector that are so lacking in this country.